Surrogate Mother (Ibu Pengganti) Dalam Perspektif Hukum Di Indonesia - Ariyanti; Rahayu, Dewi Ayu (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2022)
Having children is the dream of every married couple, but it cannot be denied that there are circumstances in which a wife cannot conceive because of abnormalities in her uterus. Technological developments in the medical field have found a new method, namely artificial insemination or what is known as in vitro fertilization (IVF). In line with in vitro fertilization (IVF) fertilization which is increasing rapidly, the Surrogate mother method has emerged, namely a woman who is willing to rent her womb, with an agreement to conceive, give birth, and give back her baby in exchange for a number of materials. to married couples who cannot have children because the wife cannot conceive. This process is constrained by the prevailing laws and regulations as well as ethical considerations and norms that apply in Indonesia. To find out whether surrogate mothers in Indonesia are permitted or not, it will be studied from civil law, health law and Islamic law. The purpose of this study is to examine and analyze the regulation of Surrogate mother (surrogate mother) according to civil law, health law and compilation of Islamic law in Indonesia. The research method used in this study uses normative legal research methods.